Should PHA practitioners take credit to mitigative safeguards to reduce the impact of an accident when performing qualitative risk analysis?. Issue 4 (23rd March 2019) - Silva, Elisio Carvalho
Abstract : Process hazard analysis (PHA) is important tool to identify the hazard and analyze the risk of a scenario. The risk is a function of the severity and frequency of occurring a loss event. Scenarios with high severity have the possibility to cause severe damage to people, environment and property. However, some companies have missed these scenarios because after applying mitigative safeguards, they have reduced the severity. Thus, these companies have lost the opportunity to draw plan to manage scenarios with high consequences, even if they are scenarios with a low frequency of occurrence. This paper aims to discuss how PHA practitioners should proceed when setting mitigative safeguards. Additionally, it proposes some actions to strengthen the process safety after identifying scenarios with high consequences. © 2019 American Institute of Chemical Engineers Process Saf Prog: e12049 2019